1995
DOI: 10.1007/bf03401891
|View full text |Cite
|
Sign up to set email alerts
|

VH3-21 B Cells Escape from a State of Tolerance in Rheumatoid Arthritis and Secrete Rheumatoid Factor

Abstract: Background: Rheumatoid factor (RF) is a characteristic but not pathognomic feature in patients with rheumatoid arthritis (RA). It is unknown whether the repertoire of immunoglobulin genes utilized by RF+ B cells of RA patients is unique and whether RF+ B cells in normal individuals are silenced or deleted. Materials and Methods: Clonal B cell populations were established from the peripheral blood of normal donors (127 B cell clones), RA patients (113 RF-and 60 RF+ B cell clones) and patients with primary Sjogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…9,11,12 V H 3-21 and V H 4-34 both have been observed to be associated with autoimmune diseases, and the preferential usage of V H genes in lymphomas may indicate that antigens are involved in the development of those tumors. [30][31][32] In our study, the five V H genes used most frequently (V H 3-21, V H 4-34, V H 3-33, V H 3-7, V H 3-53) showed a balanced distribution in mutated and unmutated cases. Therefore, a possible antigen-dependent process with selection of V H genes probably has no influence on the mutation status of the V H genes.…”
Section: Discussionsupporting
confidence: 47%
“…9,11,12 V H 3-21 and V H 4-34 both have been observed to be associated with autoimmune diseases, and the preferential usage of V H genes in lymphomas may indicate that antigens are involved in the development of those tumors. [30][31][32] In our study, the five V H genes used most frequently (V H 3-21, V H 4-34, V H 3-33, V H 3-7, V H 3-53) showed a balanced distribution in mutated and unmutated cases. Therefore, a possible antigen-dependent process with selection of V H genes probably has no influence on the mutation status of the V H genes.…”
Section: Discussionsupporting
confidence: 47%
“…B cells with RF activity generated under these culture conditions are likely related to the RF autoantibody seen in seropositive patients. Although most of these RFs are of the IgM isotype and express an Ig heavy chain in germline configuration with few mutations, they are relatively monospecific and do not widely cross-react on a panel of antigens (11). These data suggest that RFs are not natuFal autoantibodies that may have been nonspecifically activated as part of the inflammatory response in RA.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, the repertoires of RF+ B cells responsive to activated T cells and the SED-driven B cells are strikingly similar in RA patients (10). Data on the molecular structure of antibodies with RF specificity have suggested that the SED-responsive B cells of normal controls and the repertoire of RF+ B cells in RA patients are related (11,16). RF+ B cells from RA patients, which have grown in vitro by co-culture with anti-CD3-stimulated T cell clones, express the same preferential usage of the V,3 family and, in particular, of the V3-21 element as do B cells established from normal controls after SED stimulation (1 1,18).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Although it has been reported that V H 3 and V H 4 with highly mutated CDR are used in AMA, [9][10][11] and V H 3-21, V H 3-23 are used also in both the patient-and the XenoMouse-derived AMA HmAbs, the CDRs of these AMAs are distinct. Analysis of the Ig gene repertoire used by the human-type monoclonal antibodies generated in this study showed a restricted repertoire in their CDRs.…”
Section: Discussionmentioning
confidence: 99%